2003
DOI: 10.1071/aj02072
|View full text |Cite
|
Sign up to set email alerts
|

Migration, Leakage and Seepage Characteristics of the Offshore Canning Basin and Northern Carnarvon Basin: Implications for Hydrocarbon Prospectivity

Abstract: RadarSat and ERS Synthetic Aperture Radar (SAR) satellite data have been used for oil slick mapping as part of a systematic interpretative study of the offshore Canning Basin, as well as part of the northern Carnarvon Basin, extending from the inner shelf to the abyssal plain. These seepage data have been integrated with regional geological data, more than 12,000 km of reprocessed Airborne Laser Fluorosensor (ALF) survey data, seismic DHI indicators, water column geochemical sniffer data, potential field data,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…This clustering may be related to minor fault reactivation and seal failure along this major fault system. Another clustering of slicks is located along the Bonaparte-Browse Transition Zone, though the significance of these slicks has been discussed elsewhere by O'Brien et al (2003).…”
Section: Sar Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…This clustering may be related to minor fault reactivation and seal failure along this major fault system. Another clustering of slicks is located along the Bonaparte-Browse Transition Zone, though the significance of these slicks has been discussed elsewhere by O'Brien et al (2003).…”
Section: Sar Resultsmentioning
confidence: 97%
“…Finally, coral spawning might be expected to produce an abundance of slicks over, as well as around the edges of, the banks, but this is not observed. Other supporting factors for a seepage origin include the fact that many of the banks/reefs that have slicks around them have been drilled and they typically had strong shows/residual columns at reservoir level, as well as abundant gas chimneys on seismic data; some even had abundant thermogenic hydrocarbons in the seafloor sediments located directly under the slicks (O'Brien et al, 2003). If these slicks are not seepage-related, then it would seem much more likely that they are due to laminar flow or other topography-related flow processes around the reef and banks, rather than coral spawning.…”
Section: Sar Resultsmentioning
confidence: 98%
“…5). A bathymetric/current flow interpretation is also favoured for SAR slicks on the southern edge of the Bedout Sub-basin in the central North West Shelf (Jones et al, 2007), which were previously suggested to be related to hydrocarbon seepage at the edge of the regional seal (O'Brien et al, 2003c). In contrast, a coral spawning event appears to have contributed to the formation of annular to crescent-shaped SAR slicks associated with submerged reefs and shoals over the Browse-Bonaparte basin transition zone (Jones et al, 2005b.…”
Section: Satellite-based Remote Sensing Studiesmentioning
confidence: 95%
“…Assessments of natural hydrocarbon seepage that have included interpreted SAR slicks have been documented for the Timor Sea (O'Brien et al, , 2003a(O'Brien et al, , 2003bJones et al, 2005bJones et al, , 2006Rollet et al, 2006), the central North West Shelf (O'Brien et al, 1998b(O'Brien et al, , 2003cJones et al, 2007), the Great Australian Bight (Struckmeyer et al, 2002) and the Arafura Sea .…”
Section: Satellite-based Remote Sensing Studiesmentioning
confidence: 98%
See 1 more Smart Citation